Association between levels of sports participation and oral injuries among combat athletes - Hadizadeh, M.; Azri, I. D. M.; Mohafez, H.; Hafiz, E. B.; Sugajima, Y.; Azri, M. D. M. (Revista Brasileira de Medicina do Esporte, 2021)
Introduction: Oral injuries are common traumas in combat sports due to the aggressive nature of both offense and defense. Sports mouth guards are made to reduce the risk of traumatic face and jaw injuries and concussions during sports activities. Objective: The objective of this study was to determine the prevalence of oral injuries in combat sports and to examine the association between participation levels and percentage of injury occurrence. Methods: One hundred and eight participants (mean age: 22.42 ± 2.162 years) who were involved in sparring events were recruited. Data were collected using a questionnaire consisting of 22 questions about the demographic profile of the athletes, their injury experience and type of injuries sustained, awareness and use of mouth guards in sports activities. Descriptive analysis, Chi-square test, and one-way analysis of variance (ANOVA) were applied for data analysis. Results: Almost 77% of participants had experienced oral injuries during sports activities and nearly 90% were aware that oral injuries can be reduced by using mouth guards. In addition, 52.7% of participants complained that the mouth guard is not comfortable to use during sports activities. Findings revealed a significant moderate association between levels of participation and number of oral injuries ( p = 0.013). One-way ANOVA showed a significant mean difference in the rate of oral injury for the four levels of participation groups F (3, 104) = 6.21, p = 0.011. Post-hoc comparisons using the Bonferroni test indicated a significant mean difference between university-state levels ( p = 0.033) and university-national levels ( p = 0.028). Conclusion: This study revealed that higher levels of participation in sports have a higher risk of injury. It was also found that the discomfort of using a mouth guard can be reduced if the coaches make the athletes wear proper mouth guards that follow the recommended specifications.